1984
DOI: 10.1002/j.1551-8833.1984.tb05267.x
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Aluminum in Drinking Water*

Abstract: A random selection of 186 water utilities was used for this study in which raw and finished water samples were collected from each facility five times throughout a year and analyzed for iron and aluminum by atomic absorption techniques. The water samples were categorized by the supply source (ground, surface, or a combination of both), the type of water (raw, finished, or untreated distribution samples), and the type of coagulation used in the treatment process (aluminum sulfate, ferric chloride, other coagula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
10

Year Published

1985
1985
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(74 citation statements)
references
References 8 publications
0
62
0
10
Order By: Relevance
“…The pH increases slightly with increasing concentrations of the Moringa coagulant even though Muyibi & Evison (1994) observed very high doses (400-750mg/l) of Moringa in the complete removal of total hardness in water at no significant increases in pH values. However, as earlier mentioned, high dosage of alum in water treatment even though a better coagulant may lead to high acidity raising health concerns about alum related diseases reported by several investigators (Miller et al,1984, Martyns et al,1998& Najm et al, 1998. Doer (2005) reported that the action of M. oleifera as a coagulant lies in the presence of water soluble cationic proteins in the seeds (Table 2).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The pH increases slightly with increasing concentrations of the Moringa coagulant even though Muyibi & Evison (1994) observed very high doses (400-750mg/l) of Moringa in the complete removal of total hardness in water at no significant increases in pH values. However, as earlier mentioned, high dosage of alum in water treatment even though a better coagulant may lead to high acidity raising health concerns about alum related diseases reported by several investigators (Miller et al,1984, Martyns et al,1998& Najm et al, 1998. Doer (2005) reported that the action of M. oleifera as a coagulant lies in the presence of water soluble cationic proteins in the seeds (Table 2).…”
Section: Discussionmentioning
confidence: 98%
“…However, the 100% alum dose solution moved towards more acidicity attributable to the fact that alum produces sulphuric acid in solution which lowers the pH values. This tendency towards increase in acidity could also be due to trivalent cation aluminum which serves as a lewis acid that can accept a lone pair of electrons (Miller et al, 1984). The reverse was observed when Moringa concentration of the dosing solution was increased.…”
Section: Discussionmentioning
confidence: 99%
“…Crushed seeds are a viable replacement of synthetic coagulants (Kalogo et al, 2000). In Sudan, seed crude extract is used instead of alum by rural women to treat the highly turbid Nile water because of a traditional fear of alum causing gastrointestinal disturbances and Alzheimer's disease (Crapper et al, 1973;Miller et al, 1984;Martyn et al, 1989;Muyibi, 1994).…”
Section: Moringa Seeds As Coagulantmentioning
confidence: 99%
“…Aluminum is normally present in raw water; the concentrations are usually low in ground waters and are almost always high in surface waters (22). Acid rain markedly increases the "natural" aluminum content of water.…”
Section: Watermentioning
confidence: 99%